Peranan Kombinasi Pakan Limbah Organik terhadap Laju Pertumbuhan dan Kandungan Nutrisi Larva Lalat Tentara Hitam (Hermetia Illucens) - Ayuningrum, Sri Utami; Putra, Ramadhani Eka (MANILKARA: Journal of Bioscience, 2023)
The amount of organic waste is increasing along with the increase in population. The problem of organic waste can be overcome by the bioconversion method using Black Soldier Fly (BSF) Hermetia illucens larvae. This study aims to analyze the effect of combination feed with differences on the major nutrient content on survival rate, growth rate, feed consumption, Waster Reduction Index (WRI), Efficiency of Conversion of Digested Feed (ECDF), and nutritional content of BSF larvae. The feed given are  fish offal (high in fat), tofu pulp (high in protein), and banana peel (high in hemicelulose) with a ratio of 2:1:1, 1:2:1, 1:1:2, and 1:1:1. Feed combination 1:1:2 has the highest value of growth rate (3.47 mg/larva/day), feed consumption (25,76%), WRI (0,42%/day), ECDF (12.91%) and survival rate (81,38%). BSF larvae is potential to be used as alternative animal feed because they contain high levels of protein.